A retrospective review of α-gal syndrome complicating the management of suspected pancreatic exocrine insufficiency in one gastroenterology clinic in central Virginia - Richards, Nathan E.; Wilson, Jeffrey M.; Platts-Mills, Thomas A. E.; Richards, Robert D. (Frontiers in Gastroenterology, 2023)
The alpha-gal mammalian meat allergy, α-gal syndrome, often includes diarrhea, abdominal pain and other gastrointestinal (GI) symptoms. Pancreatic exocrine insufficiency causes similar symptoms. The pancreatic replacement enzymes, referred to here as pancreatic enzymes, used to treat pancreatic insufficiency are porcine products and contain α-gal. Patients with pancreatic insufficiency who also have α-gal syndrome may be intolerant of mammalian products in their diet and of α-gal in pancreatic enzymes. Here we describe 40 patients of one GI clinic in central Virginia with suspected pancreatic insufficiency and elevated α-gal IgE titers. Over 50% of these patients had some clinical improvement with stopping mammalian products in the diet. Most patients could tolerate pancreatic enzymes, 10% could not due to suspected allergy symptoms, but none developed anaphylaxis. An understanding that α-gal syndrome can be superimposed upon pancreatic exocrine insufficiency and exacerbate symptoms, and that treatment with pancreatic enzymes may increase GI and/or allergy symptoms in this group, will lead to improved medical management of this complex patient population.